EXTH-49. FOCUSED ULTRASOUND AND 5-ALA MEDIATED ELIMINATION OF DIFFUSE MIDLINE GLIOMA. (12th November 2021) - Schaab, Luana; Ferry, Yann; Ozdas, Mehmet; Kritzer, Bettina; Mourabit, Sulayman; Marcus, Stuart; Nazarian, Javad
Abstract: Diffuse midline glioma (DMG) is a devastating and incurable childhood brain cancer. With a median survival of only 9 to 11 months, over 90% of children affected by DMG die within two years of diagnosis. Despite decades of research and a growing understanding of the biology of these tumors, there have been no advancements in therapies for DMGs. Tumor heterogeneity and diffuse infiltration in inoperable brain regions make these tumors uniquely difficult to manage both surgically and pharmacologically. Therefore, there is an urgent need for the exploration of novel treatment regimens. Focused Ultrasound (FUS) is an emerging technology with significant clinical potentials. Sonodynamic therapy (SDT) is an up-and-coming treatment strategy aiming to non-invasively eliminate tumor cells by acting through compounds known as sonosensitizers, which render tumor cells sensitive to ultrasound energy. Recently, 5-Aminolevulinic acid (5-ALA), an FDA-approved molecule, has been proposed as a sono-sensitizing agent. 5-ALA mediated SDT prolonged survival in C6 rat glioma models by selective elimination of tumor cells upon sonication. Mechanistically, it is thought that 5-ALA uptake and metabolic conversion into Protoporphyrin IX (PpIX) occurs preferentially in tumor cells due to differential activity of enzymes involved in heme metabolism. Here, we investigated SDT in DMG cells treated with 5-ALA. PpIX fluorescence increased linearly up to 24 h upon 5-ALA treatment and accumulated significantly more (1.6-fold, p < 0.01) when compared to C6 cells. Consequently, FUS sonication of 5-ALA treated DMG cells at 250 kHz significantly (p < 0.05) decreased DMG cell viability compared to treatment with 5-ALA or FUS alone. Here, we show the first 5-ALA mediated sonodynamic effect in DMG cells, leading to enhanced cell death. Our findings provide a rationale for considering clinical investigation of 5-ALA mediated sonodynamic therapy in DMG.